STUDI PENGHEMATAN ENERGI PADA UNIT KETEL UAP DI PABRIK GULA - Rosyid, O A; w, Pudwo; F, diding (Badan Pengkajian dan Penerapan Teknologi, 2008)
This paper presents an energy saving study result conducted in a sugar factory located in the East Java of Indonesia. Formerly, the sugar factory was designed to fulfil their energy demand by using an abundance free energy sources, called “baggase”. However, a fossil fuel consumption (i.e. residue) increased sharply to supply boilers due to the baggase availability was not sufficient. It impacted to the increasing of operational costs. Therefore, an energy saving study for the factory had been an interesting subject. The study proposed to assess boilers performance in the factory to reduce residue consumption. A detail energy audit method was conducted to identify the actual energy consumption, energy losses, and energy saving potential. The study results showed that energy saving potential for the boilers was about 11%. The main energy saving measures was to increase boilers efficiency from 64% to 75%. The study report also included with repairing recommendation for the boilers as well as its techno-economic analysis.